Global Financial Stability Report, March 2003 : Market Developments and Issues. (Global Financial Stability Report; Global Financial Stability Report ;, 2003)
This March 2003 issue of the Global Financial Stability Report highlights that the supportive stance of monetary policy in the major economies, coupled with more risk-averse behavior by both institutional and retail investors, has contributed to a sizable buildup of cash positions. A partial mobilization of these cash positions in the fourth quarter of 2002 helped fuel a short-lived stock market rally, led to a narrowing of credit spreads on mature and emerging bonds, and contributed to an increase in flows to emerging market borrowers.